Book use in the U.P. Statistical Center Library a bibliometric study - Javier, Victoria Linda B. (1987)
This is a study on book use applying the Morse-Chen Model to determine book ciculation characteristics of the Statistical Center Library, University of the Philippines Diliman. Using probability theory, the model can obtain unbiased estimates of book circulation and predict future circulation behavior.